Bringing music to the park: The effect of Musikiosk on the quality of public experience. (June 2021) - Steele, Daniel; Fraisse, Valérian; Bild, Edda; Guastavino, Catherine
Highlights: A soundscape intervention (Musikiosk) improved the perceived ratings of pleasant, eventful, and vibrant. Musikiosk non-users showed no downsides, and experienced higher pleasantness and mood benefits. Musikiosk reduced the mentioning of traffic noise in the pocket park. People who are noise sensitive experienced most benefits except traffic noise reduction. Musikiosk did not change existing ratings of calmness, appropriateness, and restoration. Abstract: Large parks have been studied for their tranquil and restorative properties, including in the sonic dimension. The auditory experience of users in small urban public spaces, such as pocket parks is less well understood, especially as they can contain sound sources much more reflective of dense, urban activities. Musikiosk, a soundscape intervention, was deployed in a small Montreal park that allowed users to bring their own devices and play their own content over publicly provided speakers. A questionnaire study (N = 197) revealed that users found the park more pleasant, eventful, and vibrant with the presence of Musikiosk, without an associated change in calmness or appropriateness, and better for their mood states than a typical park visit. Musikiosk also reduced the likelihood that park users mentioned hearing traffic noise. Those who were more noise sensitive experienced most of the benefits of both the park visit and Musikiosk, however it did not diminish their mentions of traffic noise. These results have implications for theories and policies concerning the sounds of public spaces.